Observation of multimode quantum correlations in fiber optical solitons - Leuchs, Gerd; et al. (Physical Review Letters, 1998)
Quantum correlations of photon numbers in different spectral components of ultrashort optical solitons have been observed experimentally. These correlations are crucial for the understanding and characterization of the internal quantum structure of soliton pulses and contribute significantly to soliton squeezing by spectral filtering. The accessible information on the nonclassical state of the correlated spectral components is discussed with the example of two modes. The method may be generalized to obtain a complete quantum description of a multimode field.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.observ